Sistema didáctico para el desarrollo de habilidades motrices finas (2024)
This document will show the research and development process of the project the Tower of colors based on the research of concepts, references and work of field used in children's pedagogy for the development of fine motor skills in children aged 4 to 6 years in their developmental stage with cognitive disabilities.